To be answered with full method
Can the following expression
![{x}^{2} - 2 \: \sqrt[]{2} x - 30 {x}^{2} - 2 \: \sqrt[]{2} x - 30](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D++-+2+%5C%3A++%5Csqrt%5B%5D%7B2%7D+x+-+30)
be factorised ? why ? If yes, write the method.
Answer this as per class 9 , Polynomials
Hitech124:
I think it can't be factorised
Answers
Answered by
75
HELLO DEAR,
![{x}^{2} - 5 \sqrt{2}x + 3 \sqrt{2} x- 30 \\ \\ = > x(x - 5 \sqrt{2} ) - 3 \sqrt{2} (x - 5 \sqrt{2} ) \\ \\ = > (x - 3 \sqrt{2} )(x - 5 \sqrt{2} ) \\ \\ = > x = 3 \sqrt{2 } \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: or \: \: \: \: \: \\ \\ \\ \: \: \: \: \: \: \: \: \: \: \: x = 5\sqrt{2} {x}^{2} - 5 \sqrt{2}x + 3 \sqrt{2} x- 30 \\ \\ = > x(x - 5 \sqrt{2} ) - 3 \sqrt{2} (x - 5 \sqrt{2} ) \\ \\ = > (x - 3 \sqrt{2} )(x - 5 \sqrt{2} ) \\ \\ = > x = 3 \sqrt{2 } \\ \\ \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: or \: \: \: \: \: \\ \\ \\ \: \: \: \: \: \: \: \: \: \: \: x = 5\sqrt{2}](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2%7D+-+5+%5Csqrt%7B2%7Dx+%2B+3+%5Csqrt%7B2%7D+x-+30+%5C%5C+%5C%5C+%3D+%26gt%3B+x%28x+-+5+%5Csqrt%7B2%7D+%29+-+3+%5Csqrt%7B2%7D+%28x+-+5+%5Csqrt%7B2%7D+%29+%5C%5C+%5C%5C+%3D+%26gt%3B+%28x+-+3+%5Csqrt%7B2%7D+%29%28x+-+5+%5Csqrt%7B2%7D+%29+%5C%5C+%5C%5C+%3D+%26gt%3B+x+%3D+3+%5Csqrt%7B2+%7D+%5C%5C+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+or+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%5C+%5C%5C+%5C%5C+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+%5C%3A+x+%3D+5%5Csqrt%7B2%7D+)
it can be factorise by this two no.
5√2 and 3√2
we know that:-
factorisation method
splitation of middle term = multiplication of first and Last term
here,
multiplication of first and last Term = -30
and middle term = -2√2
it can also be written as, [5√2-(3√2)]=2√2
and multiply of this no. = 15×2 =-30
hence it can be factorise
I HOPE ITS HELP YOU DEAR,
THANKS
it can be factorise by this two no.
5√2 and 3√2
we know that:-
factorisation method
splitation of middle term = multiplication of first and Last term
here,
multiplication of first and last Term = -30
and middle term = -2√2
it can also be written as, [5√2-(3√2)]=2√2
and multiply of this no. = 15×2 =-30
hence it can be factorise
I HOPE ITS HELP YOU DEAR,
THANKS
Answered by
58
Yes, The following polynomial can be factorised .
It can be factorised by splitting the middle term.
=x²-2√2x-30
= x²-5√2x+3√2x-30
= x( x - 5√2) + 3√2 ( x - 5√2 )
= ( x - 5 √2 ) ( x +3√2 )
Hope helped!
It can be factorised by splitting the middle term.
=x²-2√2x-30
= x²-5√2x+3√2x-30
= x( x - 5√2) + 3√2 ( x - 5√2 )
= ( x - 5 √2 ) ( x +3√2 )
Hope helped!
Similar questions